Deficiência intelectual e sexualidade: a violência sexual em foco - Mendes, Marlon Jose Gavlik (2022)
Sex, sexuality and disability are complex phenomena, present in everyone's lives, but manifesting themselves in different ways. These phenomena are permeated by knowledge and powers and can motivate episodes of aggression. Sexual violence is any sexual act that involves coercion, intimidation, threats or blackmail, and is carried out without the consent of the other person. Sexual exploitation is the forced involvement of minors in situations of prostitution or forced marriage. There is a high incidence of this violence today, especially among female adolescents, however there are few studies that investigate this violence aimed at people with disabilities. This gap in Brazilian scientific production prompts questions to Brazilian researchers and unfolds in research possibilities, such as the vulnerability of people with disabilities to situations of sexual violence and their knowledge about violence, sex and sexuality. Thus, the general objective of this research was to investigate the vulnerability of young people with intellectual disabilities in the face of situations of sexual violence and to identify the knowledge of these young people and their guardians and teachers about sexuality, sex, sexual violence and its prevention. Quali-quantitative methods of data collection and analysis were used. Initially, the “What if – Situations test” instrument was applied to nine young people diagnosed with intellectual disabilities residing in the interior of the state of São Paulo to investigate their vulnerability to situations of sexual violence. Semi structured interviews were also carried out with these young people, their guardians and their teachers, addressing topics about sex, sexuality, sex education and protection from sexual violence. The collected data were systematized and analyzed qualitatively using genealogy under a Foucaultian understanding. The results showed that young women demonstrate considerable vulnerability to sexual violence, with difficulties in recognizing situations that indicate danger and in acting in the face of these situations. Their responses to situations of danger were permeated by social constructions of gender, approaching socially required performances of the male and female gender. The speeches of the guardians circulated about the overprotection of their children, constituting a system of surveillance and control of the body, and in infantilizing and asexual notions of disability. The teachers also noticed these speeches by the guardians, and they try to do orienting work with the students, however their performance is permeated by the control and surveillance of the body and by the hypersexualizing discourses of disability. Both teachers and guardians say they do not work on preventing violence with young people, giving vague and not very assertive guidelines on sexual violence. The intersection between the studies of sexuality, violence and disability is an unexplored field, however rich in contributions to professional practice and to the fight against violence. It is hoped that this thesis has contributed to these questions.